Insecticidal Potentials of Black Seed, (Nigella Sativa) Powder as an Eco-Friendly Bio-Pesticide in the Management of Dermestes Maculatus in Codfish Gadus Morhua (Gadidae: Gadiformes) - Esther Bethel Aalonee; Rosetta Bekinwari Bob-Manuel; Judith Awele Chekwube Nwanze; Usman Zakka (Zenodo, 2023)
This paper reviewed public health interventions for effective breast feeding as a strategy to improve child health and reduce morbidity/mortality among children. The importance of breast feeding is overwhelming and cuts across the mother, child, community and the nation at large. Breast milk is the first food for the start of life. The milk has all the nutrients required for growth and development, hence the child should not be denied the pleasure. The national policy on food and nutrition recommends that 50% exclusive breastfeeding rate be achieved by 2025 following the WHO 1981 Code for safe and adequate nutrition. To achieve this, every year globally, breast feeding week is celebrated and each year has its theme. The 2021 world breastfeeding week was marked in the first week of August with the theme ‘Protect Breastfeeding: A Shared Responsibility”. The 2022 world breast feeding week was held from the 1st – 7th of August with the theme “Step up for breast feeding: Educate and support”. This paper has explained some public health interventions such as health education, advocacy, focus group discussion, peer counselling, health facility and home-based activities among others for promotion and sustenance of breast feeding.